Development of Regulatory Recommendations for City Bus Bumper Bars through Design and Analysis Based on Standard 67 Pa. Code § 171.44 - Sukoco, Leonardo Paksi; Aravy, Mochammad Avrieza Havies; Banna, Nurrahim Hasan Al; Winesti, Feby Ayu (Piston: Journal of Technical Engineering, 2026)
Indonesia currently does not have specific technical regulations governing the design of urban bus bumper bars, unlike passenger vehicles, which are regulated by national and international standards. Data from the Indonesian National Police Traffic Corps in 2022 recorded 3,847 bus-related accidents resulting in 587 fatalities, with 42 percent occurring in urban areas at speeds ranging from 30 to 50 km/h. This study aims to develop regulatory recommendations for urban bus bumper bars by adapting the standard 67 Pa. Code §171.44 to Indonesian operational conditions. The research methodology includes field observations of 10 Trans Jogja buses, bumper bar design using a combination of 6061-T6 aluminum alloy and elastomer materials, and structural performance analysis through impact simulations based on the Explicit Dynamics finite element method using ANSYS software. The simulation results show that the proposed bumper bar design satisfies safety requirements, with maximum stress values of 260 MPa at 30 km/h and 293 MPa at 50 km/h. Although the stress at 50 km/h exceeds the material yield strength of 280 MPa, the response indicates localized plastic deformation without global structural failure. Controlled deformation of 163.04 mm at 30 km/h and 275.78 mm at 50 km/h, following a localized progressive deformation pattern without excessive intrusion, along with an energy absorption capacity of at least 5 kJ, demonstrates effective passenger protection. The resulting regulatory recommendations include dimensional specifications (height 400–600 mm, width ≥2000 mm), material requirements (yield strength ≥250 MPa), and performance criteria to support the revision of Minister of Transportation Regulation No. 33 of 2018.